Analysis of consumers’ preference on taro-flavored UHT Ultra milk using conjoint method in Malang City - Azimmatul Ihwah; Rahmadilla Alif Madia Putri; Ika Atsari Dewi; Panji Deoranto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
One of the processed milk products is Ultra Taro UHT milk. The aim of this research was to analyze Ultra Taro UHT milk’s importance level of attributes and combinations of the attributes which are preferred based on consumer preferences. This study was quantitative correlational using a questionnaire with a full profile presentation method. The study was conducted for one month, with 60 respondents determined by the purposive sampling method. Data was processed using the conjoint method. In this research, 4 product attributes were used, there are flavor with 3 levels, volume with 3 levels, fat content with 2 levels, and type of packaging with 2 levels. The results showed the level of importance value, attribute flavor with a relative value of 34.44%, volume and packaging types have similar relative value of 27.79%, and fat content with a relative value of 9.97%. The combination of attributes favored by consumers was the fifth stimuli with a total use value of 3.8283 consisting of taro balanced milk flavor attributes, 200 ml volume contents, low fat, and tetra pack packaging types. The results of the conjoint have significant correlation with the opinion of respondents with a positive Kendall Tau correlation value of 0.889.